The Effect of Stork Balance Test Exercise To Resilience Composition Body Athlete Persema Football - Satriya, Hendra Putra; Pamungkas, Hari; Nidomuddin, Muhammad; Mardikaningsih, Agusti; Saputro, Yulianto Dwi (Jurnal Pendidikan Jasmani (JPJ), 2025)
Study This aiming for know influence exercise Stork Balance Test to resistance and composition body athlete club football​ Persema. Balance training is part important in the training program athletes, especially in the sports branch sport like demanding football​ stability body, coordination, and efficiency movement. The research method used is experiment quasi- experiment with pre-test and post-test design on one group. The sample consists of from 20 athletes selected football​ purposively. Stork Balance Test Exercise given for 6 weeks with frequency 3 times per week. Instrument measurement covering test endurance (multistage fitness test) and analysis composition body (percentage of body fat and mass) muscle). Research results show existence significant improvement in resilience​ physical and changes positive on composition body athlete after undergo an exercise program. With Thus, practice balance use method Stork Balance Test can become part effective in the training program physique athlete football for​ increase performance in a way comprehensive.